2022
DOI: 10.22515/sustinerejes.v6i2.187
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of built-up area and land surface temperature in Surakarta using Landsat imageries

Abstract: The need for built-up areas continues to increase, along with the increasing population in the city of Surakarta and its surrounding. This condition affects the land surface temperature which then leads to the change in climatic conditions. The availability of land for settlement and surface temperature will affect the comfort level of living in a city. For this reason, this study aims to map the distribution of built-up area and the surface temperature of Surakarta city and discusses the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The generated LST also show that the highest LST is in the city centre and decreases as it moves towards the outskirts of the city. These trends are similar with the research findings from Saputra, Ibrahim, Shofirun, Saifuddin and Furoida [13] and Fikriyah, Danardono, Sunariya, Cholil, Hafid and Ismail [2]. The visualisation of NDWI (Figure 3 and Figure 4) shows that there is a lot of red indicating high value in the city center, but the green colour which indicates the low value equally dominates.…”
Section: Performance Of Various Spectral Indices As Lst Indicatorssupporting
confidence: 88%
See 2 more Smart Citations
“…The generated LST also show that the highest LST is in the city centre and decreases as it moves towards the outskirts of the city. These trends are similar with the research findings from Saputra, Ibrahim, Shofirun, Saifuddin and Furoida [13] and Fikriyah, Danardono, Sunariya, Cholil, Hafid and Ismail [2]. The visualisation of NDWI (Figure 3 and Figure 4) shows that there is a lot of red indicating high value in the city center, but the green colour which indicates the low value equally dominates.…”
Section: Performance Of Various Spectral Indices As Lst Indicatorssupporting
confidence: 88%
“…Moreover, since built-up area growth has an association to the energy consumption and urban heat, a quantitative measurement of built-up area, in terms of its distribution, and expansion, is therefore important as an attempt to support city planning and management. In addition, green space mapping is also crucial in order to maintain the sustainability of a city [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the built-up area, NDBI characteristics can be seen: objects will appear higher in the middle infrared channel than the near infrared channel (Zha et al, 2003). Finding NDBI can be done by using the following equation (Fikriyah et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies stated that urbanization contributes to environmental degradation. Research by Fikriyah & Sunariya (2022) found that built-up density has a correlation with land surface temperature. Furthermore, Khoshnevis Yazdi & Dariani (2019) stated that the population is living in urban area cause two-thirds of greenhouse gas, which contain carbon dioxide emission (CO2) in it.…”
Section: Introductionmentioning
confidence: 99%